Toward a conceptual framework for arts-based peacebuilding : the contributions of nonscripted theater(sic) and hip hop music - Cohen, Adar (Irish School of Ecumenics, 2010)
Various approaches to research are engaged dynamically and according to the unique challenges presented by developing a framework for understanding how the arts contribute to peace. The principal research methods of this writing include participant observation, ethnography, participatory action research, and interdisciplinary theoretical research.
Keywords: Ecumenics, Ph.D.; Ph.D. Trinity College Dublin.